Analysis of The Consideration of The Judges over A Suit Violating The Law in Palembang State Of Court (The Study Of Decision No. 166/Pdt.G/2016/PN.Plg) - Efka Firsta (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2018)
The doctrine of violating the law (onrechtmatige daad) is regulated in Article 1365 of the Civil Code from narrow teachings which interpret that the nature of illegal acts (onrechtmatige daad ) is similar to acts against laws or written law, has developed into a broad teaching. Violation of Article 1365 of the Criminal Code The person who commits a violation of the law and causes a loss shall be obliged to compensate the said loss. Compensation can be in the form of money, restored to its original state, the claimant is entitled to request that the judge stated that the act was an unlawful act atu su s ebagaimana lawsuit in Pu decision- No. 166/Pdt.G/2014/PN/Plg. The plaintiff's party has stated that the defendant's actions violated Article 1365 of the Civil Code but the judge refused as an illegal act. The court not only decides the case procedurally but needs to have a legal breakthrough as a step of legal discovery (rechtvinding) so that it covers the frame of mind as a legal reasoning about how the judge must decide on a case. The research using normative and based on secondary data to support success. Based on this, a problem was found on the basis of the judge's consideration so that the Plaintiff's Violating Action Act in the above case was rejected by the Palembang District Court Judge as in Decision No. 166/Pdt.G/ 2014/PN.Plg.Keywords: violating the law; lawsuit; compensation